Nanomaterials Enhance the Immunomodulatory Effect of Molecular Targeted Therapy - Li Z (Dove Medical Press, 2021)
Zhongmin Li, Yilun Liu, Xuedong Fang, Zhenbo Shu Department of Gastrointestinal Colorectal and Anal Surgery, China-Japan Union Hospital of Jilin University, Changchun, 130033, People’s Republic of ChinaCorrespondence: Zhenbo Shu Email shuzb@jlu.edu.cnAbstract: Molecular targeted therapy, a tumor therapy strategy that inhibits specific oncogenic targets, has been shown to modulate the immune response. In addition to directly inhibiting the proliferation and metastasis of tumor cells, molecular targeted drugs can activate the immune system through a variety of mechanisms, including by promoting tumor antigen processing and presentation, increasing intratumoral T cell infiltration, enhancing T cell activation and function, and attenuating the immunosuppressive effect of the tumor microenvironment. However, poor water solubility, insufficient accumulation at the tumor site, and nonspecific targeting of immune cells limit their application. To this end, a variety of nanomaterials have been developed to overcome these obstacles and amplify the immunomodulatory effects of molecular targeted drugs. In this review, we summarize the impact of molecular targeted drugs on the antitumor immune response according to their mechanisms, highlight the advantages of nanomaterials in enhancing the immunomodulatory effect of molecular targeted therapy, and discuss the current challenges and future prospects.Keywords: nanomaterial, molecular targeted therapy, immunomodulation, immunotherapy, cancer therapy